The Caliph as a Head : Tjokroaminoto’s Political Thought in the 1920s - Waginugroho, Septian Anto (Tarikh : Journal of Islamic History and Civilization, 2025)
The purpose of this study is to analyze H.O.S. Tjokroaminoto's political thoughts on the caliphate in the 1920s, in the context of global caliphate issues after the abolition of the Ottoman Caliphate in 1924. As an intellectual with a background as a santri-priyayi (Islamic scholar-noble), a skilled orator, and leader of Sarekat Islam, Tjokroaminoto viewed the caliphate as the “head” of the ummah—an important moral-political authority for maintaining the dignity of Islam under colonial domination. This view was shaped by his biographical experiences, his ideological understanding of Islam, and his involvement in the dynamics of global Islamic activism. For Tjokroaminoto, Islam and politics were inseparable; Islam encompassed not only spiritual and religious aspects, but also social and political issues. This study places the caliphate crisis in its historical context, examines the response of Muslims in the Dutch East Indies, and highlights Tjokroaminoto's role and thoughts on the issue. Tjokroaminoto's ideas on the caliphate had a major influence in shaping the boundaries and direction of political Islam in Indonesia in the early 20th century, as well as having a significant impact on Muslims at that time.